2008
DOI: 10.1074/jbc.c800055200
|View full text |Cite
|
Sign up to set email alerts
|

S6K1 Phosphorylates and Regulates Fragile X Mental Retardation Protein (FMRP) with the Neuronal Protein Synthesis-dependent Mammalian Target of Rapamycin (mTOR) Signaling Cascade

Abstract: Fragile X syndrome is a common form of cognitive deficit caused by the functional absence of fragile X mental retardation protein (FMRP), a dendritic RNA-binding protein that represses translation of specific messages. Although FMRP is phosphorylated in a group I metabotropic glutamate receptor (mGluR) activity-dependent manner following brief protein phosphatase 2A (PP2A)-mediated dephosphorylation, the kinase regulating FMRP function in neuronal protein synthesis is unclear. Here we identify ribosomal protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
230
1
10

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(253 citation statements)
references
References 46 publications
12
230
1
10
Order By: Relevance
“…and synaptic levels of the corresponding transcripts, SAPAP1 and SAPAP3 are more abundant at neocortical and hippocampal synapses of adult Fmr1 Ϫ/Ϫ mice, respectively. Consistently, an elevated SAPAP3 concentration was observed in hippocampal lysates of FMRP-deficient mice (68). Here we also show that mRNAs encoding SAPAP1-3 are in vivo brain targets of FMRP.…”
Section: Discussionsupporting
confidence: 66%
“…and synaptic levels of the corresponding transcripts, SAPAP1 and SAPAP3 are more abundant at neocortical and hippocampal synapses of adult Fmr1 Ϫ/Ϫ mice, respectively. Consistently, an elevated SAPAP3 concentration was observed in hippocampal lysates of FMRP-deficient mice (68). Here we also show that mRNAs encoding SAPAP1-3 are in vivo brain targets of FMRP.…”
Section: Discussionsupporting
confidence: 66%
“…[7][8][9][10][11][12][13] A bimodal intellectual quotient (IQ) distribution in the total TSC population has been suggested 7 and was recently refined as being observed only in the TSC2 population. 10 TSC patients with germline TSC1 and TSC2 mutations have only one fully functional TSC2 allele in all their cells, and this condition could lead to neurocognitive dysfunction through the mechanism of haplo-insufficiency, [14][15][16] similar to Fragile-X syndrome and Neurofibromatosis type 1. [14][15][16] However, in TSC there are additional factors which may contribute to cognitive impairment, including loss of heterozygosity, which may contribute to tuber development, 17,18 and effects of early onset and refractory epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…10 TSC patients with germline TSC1 and TSC2 mutations have only one fully functional TSC2 allele in all their cells, and this condition could lead to neurocognitive dysfunction through the mechanism of haplo-insufficiency, [14][15][16] similar to Fragile-X syndrome and Neurofibromatosis type 1. [14][15][16] However, in TSC there are additional factors which may contribute to cognitive impairment, including loss of heterozygosity, which may contribute to tuber development, 17,18 and effects of early onset and refractory epilepsy. Thus far, no associations have been found between specific TSC mutation types and cognitive outcomes, 10,19 although there are reports on associations with epilepsy and psychiatric features.…”
Section: Introductionmentioning
confidence: 99%
“…RNA extracted from immunoprecipitates was probed for Jacob, SAPAP3, and BC1 RNAs by RT-PCR and real time RT-PCR. SAPAP3-and BC1-specific amplifications served as positive and negative controls for FMRP-associated RNAs, respectively (19,24,25). RT-PCR data showed that Jacob and SAPAP3 mRNAs were present in both the WT-F-IP and WT-P-IP but were basically absent or only weakly detected in the KO-F-IP and WT-IgG-IP (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5B). Similar to SAPAP3 mRNAs, known FMRP targets (24,25), Jacob transcripts were found to specifically associate with FMRP (Jacob mRNA enrichment: WT-F-IP versus KO-F-IP ϭ 6.3 Ϯ 1.8 and WT-F-IP versus WT-IgG-IP 11.1 Ϯ 0.3; SAPAP3 mRNA enrichment: WT-F-IP versus KO-F-IP ϭ 9.6 Ϯ 3.6 and WT-F-IP versus WT-IgG-IP ϭ 10.8 Ϯ 0.9; n ϭ 4); and PABP (Jacob and SAPAP3 mRNA enrichment: WT-P-IP versus WT-IgG-IP ϭ 32.4 Ϯ 3.3 and 28.5 Ϯ 2.1, respectively; n ϭ 4). To analyze whether FMRP plays a role in dendritic targeting of Jacob mRNAs, we performed fluorescent in situ hybridization on cultured cortical mouse neurons.…”
Section: Resultsmentioning
confidence: 99%